An Introduction to ZABBIX, the System that Regularly Monitors Server Resources - Nguyen, Ngọc Hùng Anh; Vo , Quang Long; Tran, Minh Sơn; Tran, Thu Hà (Journal of Technical Education Science, 2022)
The article summarizes the protocols and systems used in managing and monitoring resources of server systems operating regularly 24/24 hours and 7/7 days a week, providing the most comprehensive "health" status information of the server. Zabbix, an open source application, has emerged as a versatile candidate to support diverse, centralized or distributed network connections. The article focuses first on introducing in detail the features of the Zabbix system. Then a real deployment of Zabbix in a specific application is also described: a real-time alert monitoring of unusual resource changes for the digital television system on the open Internet called OTT3A (Over The Top with 3 Adaptivities). Based on OTT technology, the OTT3A is developed by the HCMUTE reseachers with 3 new adaptivities to improve the effeciency of the video streaming over the Internet. Firstly, the bitrate adaptivity is improved with the spatial and temporal optimatisation, providing better image quality in the bandwidth incertainty of the public Internet. Secondly, broadcasted contents are ordered in a topic adaptivity for faster research of a content to be viewed. And finally, a resource adaptivity is proposed to exploit better the sub network bandwidth whenever there are a group of viewers comsumming already the same content. The system is a good usecase for benchmarking Zabbix application in daily continuous system monitoring according to the criteria: CPU’s load, percentage of memory usage, the transmission bandwidth of the 2 LAN cards, the hard drive usage status.